Factors influencing farmers’ choices of adaptation to climate change in Ekiti State, Nigeria (2014)
Climate change poses a great threat to human security through erratic rainfall patterns and decreasing crop yields, contributing to increased hunger. The perceptions of the indigenous people about climate change and their responses to climate change have significant roles to play in addressing climate change. Therefore a critical study on farmers’ choices of adaptation is critical for ensuring food security and poverty alleviation. A multi-stage random sampling technique was used to select 156 households in Ekiti state while descriptive statistics and multinomial logit (MNL) were used to analyze the data obtained from the households. The results showed that the most widely used adaptation method by the farmers were soil and water conservation technique measures (67 percent). The multinomial logit analysis revealed that the factors explaining farmer’s choices of climate change adaptation include age of the farmers, gender of the household head, years of education, years of farming experience, household size, farmers information on climate change, farmers access to credit, farm income, non-farm income, livestock ownership and extension contact.